Analysis of Potato Farmer Satisfaction Towards âXâ Fungicide in Sumberbrantas Village, Bumiaji Sub-District, Batu City - Agustyarini, Dwi Wulandari; Anindita, Ratya; Nugroho, Condro Puspo (HABITAT, 2017)
The objectives of this research are to determine the decision making process in using âXâ fungicide, the level of farmersâ satisfaction, and the loyalty level of the farmers towards âXâ fungicide. The research was carried out in Sumberbrantas Village, Batu City. The determination of the respondents was conducted by using a simple random sampling with a total of 40 respondents. The methods used in this research were descriptive analysis for the decision-making process and for the loyalty level of the farmers, importance performance analysis (IPA), and customer satisfaction index (CSI). The result of decision-making process shows that farmers have decided to use âXâ fungicide because the quality and active ingredientswithinwhile the IPA method shows that the efficiency of fungicide and the fact that there are no side effects on the plant become the top priority. On the one hand, the result of CSI method shows that 78,57% of the farmers are satisfied with âXâ fungicide. As a whole, farmers have entered the habitual buyer level.